ITIH2 in colorectal cancer metastasis: Weighted Gene Co-expression Network Analysis-guided functional validation - Xin-Feng Zhang; Xiao-Li Zhang; Hai-Wen Xu; Ya-Hui Lin; Yan Tian; Cheng Chen; Huayou Luo (PLoS ONE, 2026)
Objective One of the main causes of death from colorectal cancer (CRC) is liver metastases; yet, little is known about the genetic factors that influence the development of these metastases. Given their proven involvement in cancer spread, we anticipated that major differentially expressed genes (DEGs) between primary and metastatic CRC could identify important molecular players in liver metastasis, with an emphasis on extracellular matrix and proteolytic processes. The purpose of this study was to use integrative bioinformatics and experimental validation to identify and functionally describe hub genes linked to CRC liver metastasis. Methods The differentially expressed genes (DEGs) between primary (CRC and CRC liver metastases are investigated using two microarray datasets (GSE14297 and GSE6988). Weighted Gene Co-expression Network Analysis (WGCNA) was used to generate co-expression networks and identify functional modules associated with metastatic progression. Topological research revealed that ITIH2 is an essential hub gene. To investigate its functional role, we employed lentiviral transduction to generate stable CRC cell lines with ITIH2 overexpression and knockdown. For in vivo validation, liver metastasis models were created in BALB/c mice using engineered cell lines. To further explore clinical relevance, ITIH2 expression in tissue microarrays from patients with primary and metastatic CRC was examined immunohistochemically. Results When compared to primary tumors, ITIH2 expression was noticeably higher in CRC liver metastases. In contrast to ITIH2 knockdown, which inhibited these malignant behaviors, functional studies showed that ITIH2 overexpression increased CRC cell proliferation, motility, and invasion. These results were supported in vivo , where ITIH2 expression increased the likelihood of tumor growth and metastasis. Conclusions ITIH2 plays a functional role in metastatic behavior and is markedly elevated in liver metastases of CRC. We conclude that ITIH2 may be a novel prognostic biomarker and a potential therapeutic target in patients with CRC who have liver metastases due to its high correlation with poor clinical outcomes and independent prognostic significance for overall survival.